2009
DOI: 10.1177/0255761409345918
|View full text |Cite
|
Sign up to set email alerts
|

‘I’ll sing with my buddies’ — Fostering the possible selves of male choral singers

Abstract: The stories of three high school boys about their experiences in school-based choral music provide the framework for a discussion of the role music educators can play in retaining male singers. The 'possible selves' construct (Markus & Nurius, 1986) is explored alongside research-based implications about specific steps toward developing boys' identities as choral musicians. Possible selves are future conceptions of the self that are either positive (hopedfor) or negative (feared). The changing of the adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
1
37
0
1
Order By: Relevance
“…Beyond Cooksey, researchers associated adolescent male voice change with various topics, including participation in choir (Kennedy, 2002), attrition and retention of males in choir (Freer, 2006), male gender identity (Elorriaga, 2011), and the theory of possible selves (Freer, 2009b(Freer, , 2010. Despite different foci, each of these studies highlighted the influence (both positive and negative) of peer and teacher interactions on developing male singers as well as the importance of vocal modeling for male changing voices.…”
Section: Male Voice Changementioning
confidence: 99%
“…Beyond Cooksey, researchers associated adolescent male voice change with various topics, including participation in choir (Kennedy, 2002), attrition and retention of males in choir (Freer, 2006), male gender identity (Elorriaga, 2011), and the theory of possible selves (Freer, 2009b(Freer, , 2010. Despite different foci, each of these studies highlighted the influence (both positive and negative) of peer and teacher interactions on developing male singers as well as the importance of vocal modeling for male changing voices.…”
Section: Male Voice Changementioning
confidence: 99%
“…Structured surveys are the most widely used data-gathering tools (see Markus and Nurius 1986), with narrative techniques and those requesting visual data becoming more common (Bruner 1990;Clandinin 2006;Hollingsworth and Dybdahl 2007;Whitty 2002). Participant drawings and improvised scene acting have also been used within research concerning possible selves (Packard and Conway 2006), including projects in music education settings with adolescent boys (Freer 2009) that led to a curricular model for the identification of possible selves in music, and university teacher preparation programmes (Brand and Dolloff 2002). The latter study compared the musical and pedagogical identities of Chinese and North American methods course participants as depicted in drawings, finding that North American students held rigid, highly compartmentalised images of the distinct identities of musician and teacher, while Chinese students viewed these two identities as more fluid and interactive.…”
Section: Conceptual Framework and Possible Selvesmentioning
confidence: 99%
“…Previous narrative research with a small number of adolescent boys (n=3) identified topics associated with the development of possible selves through vocal-choral music experiences (Freer, 2009b). Each topic identified in the earlier study was found in this larger data set.…”
Section: Analysis: Topics and Interpretationsmentioning
confidence: 72%
“…These studies suggest that the development of possible selves is developmental and sequential, with six stages that progress from conception of an envisioned future self to realisation of that future self (see Hock, Deshler & Schumaker, 2006;Freer, 2009b). The six stages and descriptions are:…”
Section: The Adolescent Male Voice Change Motivation and Identity Dmentioning
confidence: 99%